The Effect of Soluble Ammonium Polyphosphate on the Properties of Water Blown Semirigid Polyurethane Foams - Weiguo Yao; Hanmo Wang; Dongbo Guan; Tao Fu; Tianqi Zhang; Yanli Dou (Advances in Materials Science and Engineering)
Soluble ammonium polyphosphate (SAPP) is employed to prepare flame retardant semirigid polyurethane foam (SPUF) using water as blowing agent. The flame retardant property of SPUF is evaluated by limiting oxygen index (LOI) and horizontal burning test. Also the thermal degradation mechanism is studied by TG and Fourier transform infrared (FTIR). The results show that, with the increase of the content of SAPP, flame retardant property of SPUF improves obviously as the LOI value increases and the horizontal burning rate decreases. And residual char is increased up to 20% with 19 wt% SAPP. Moreover, the mechanical property of SPUF is enhanced dramatically.